Colletotrichum theobromicola causing anthracnose on butia fruits in Brazil. Issue 2 (19th November 2017) - Dorneles, K. R.; Eloy, J.; Dallagnol, L. J.
Summary: Native fruits of Brazil have received more attention recently due to their organoleptic properties and as sources of secondary metabolites that improve human health. Amongst the native fruit species are Butia spp palms, the fruits of which are consumed raw or processed into juices, jams, liquor and ice cream. In this work, anthracnose was found on fruits from Butia odorata plants. Fruits heavily affected by this condition are considered inappropriate for consumption of raw or use in processed foods. The fungus was identified using morphological and molecular methods as Colletotrichum gloeosporioides, phylogenetically close to Colletotrichum theobromicola . To the best of our knowledge, this is the first report of C. theobromicola causing anthracnose in Butia species.